Implications of Seasonal Canopy Management and Growth Compensation in Grapevine - Hunter, J.J. (South African Journal of Enology and Viticulture, 2017)
The effect of eight seasonal canopy management treatments on yield and growth compensation of a vertically trellised Vitis vinifera L. cv. Sauvignon blanc/110 Richter vineyard was investigated. East-West orientated rows were spaced 2.75 x 1.5 m. Spurs were spaced 15 cm apart. Intensive micro-irrigation was applied. Canopy management comprised better accommodation of foliage on the trellising system and different means of reducing foliage during the berry set to pea berry size period of the growth season. Combinations of shoot positioningsuckering-topping and shoot positioning-suckering-topping-leaf removal resulted in the highest yields; substituting leaf removal with lateral (secondary shoot) removal noticeably decreased yields. No canopy management resulted in the lowest yields.  Based on production (and labour), lateral shoot removal cannot be considered an economically viable canopy management practice. Significant compensatory growth was induced by the removal of lateral shoots. That would have impacted on the distribution of carbohydrates and probably counterbalanced the positive effects of an improved microclimate and related. reactions. Lateral removal reduced bunch development compared to treatments that included leaf removal instead. Yield differences between treatments showed no obvious relationship with fertility or budding. Neither bunch rot nor soluble solid accumulation played a role in the yield reduction found with lateral removal. Total hexose content in the berries at ripeness was, however, reduced by lateral removal, decreasing further the earlier lateral removal was applied. For the treatments where no laterals were removed, lateral leaves made the highest contribution to the total sugar content of the leafy part of the canopy.  The ratio between the total output of the main shoot leaves and that of the lateral shoots was reversed when laterals were removed. Sugar content of leaves on main shoots of lateral removal treatments complied with the compensation theory of source:sink relationship. Apparently, shading had a pronounced effect on the total carbohydrate content of non-treated canopies. Although root starch content was not affected by lateral removal during the study period, root density was decreased, indicating limited root development. A positive relationship between root density and yield was found. Although the presence of particularly medium and small leaves and therefore the contribution of these leaves to yield was reduced by lateral removal, the total leaf area/g fruit was never less than the generally accepted norm of 12 cm2• The results indicated that available leaf area (even when well-exposed) cannot generally be accepted as the norm, but that the composition of the leaf area should be taken into account, as it has a critical role in the efficiency of the canopy and the nourishing of the bunches. Ratios of main shoot leaf area to lateral shoot leaf area as well as practical canopy composition criteria are presented. Results are also argued as to the role of hormonal activity in growth compensation and trigger mechanisms. The results provide new perspectives on existing canopy composition criteria and implications of growth compensation. The study clearly indicates the beneficial effects of correct seasonal canopy management.